Sejarah Museum Seribu Moko di Kabupaten Alor Tahun 2003-2023 - Utomo, Susilo Setyo; Ande, Andreas; Maukari, Wisye Grace Maria (FLORESIENSIS, 2022)
This research aims to find out The History of the Thousand Moko Museum in Alor District and to find out what collections are in the Thousand Moko Museum and the number of Moko stored in the Thousand Moko Museum. The type of research used is historical research. Informans in this research were determined using purposive sampling technique. The location of this research was in Kalabahi city, Teluk Mutiara Sub-district, Alor District. To obtain data in this research primary data sources and secondary data sources are needed. Data collection techniques are interviews, observation, and document study. The data analysis techniques used are heuristic, verification, interpretation, and historiography. The results of this research show that: (1) The Seribu Moko Museum was founded in 2003 and inaugurated in 2004. The name “Seribu Moko”, describes abundance, variety and hope, while “Moko”, describes traditional objects that are used by almost everyone. Layers of Alor society. The Seribu Moko Museum is under the Alor Regency Regional Government, in this case under the Culture Service. In managing this museum, because it is part of the Regional Government, there is number of budgets specifically for museum management. The development of the Seribu Moko Museum has experienced quite a lot of development. The Seribu Moko (Ct)um is still trying to make developments in order to attract the interest of visitors so that they feel comfortable when looking for information about cultural objects in the museum. (2) Moko is cultural object made of bronze which is shaped like a closed cormorant. Some theories say that Moko comes from the Dongson Culture in North Vietnam, while the Aloe people themselves believe that Moko comes from the land. Moko, which is highly valued by the people of Alor, has various shapes and decorations and some symbolize certain tribes. There are various types of cultural object collections in the Seribu Moko Museum, such as Moko, Archaeological, Numismatics, Biological, Ethnographic, Philological, Technological, Fine Arts, Ceramics, Geological, And Historical Collections.Keywords: History, Museum, Moko, Development